Indian Banking – NEW Vision 2030 - Uppal, R. K. (Journal of Education and Vocational Research, 2011)
Dynamic changes are taking place in the Indian banking industry .The purpose of this paper is to access and analyze the future of Indian banking in the coming competitive era. With the help of ratio analysis method and various statistical techniques ,evaluates the performance of banking industry .In the post – second banking reforms era, Indian banks are very fastly changing and ready to face the global challenges. The paper has been divided into two parts, i.e pre-ebanking period and post -ebanking period. The paper concludes that the performance of banks much better in the post ebanking period. Only those banks will survive in future, which are intensively using information technology in day-to-day activities. The present paper highlights the changing face of Indian banks and predicts the future for 2030. Information technology has altered the face of Indian banks and it has positively affected the productivity and profitability of banks. The presence of Indian banks in the global market is continuously increasing.